First-Year Students' Initial Understanding of The Basic Concept of Static Fluid - Dios Sarkity; Metta Liana; Cicyn Riantoni; Putri Dwi Sundari; Bakhrul Rizky Kurniawan (Jurnal Pendidikan Fisika, 2025)
Indonesia is one of the largest maritime countries in the world. Learning should be carried out contextually by linking knowledge with contexts relevant to students' daily lives, such as the maritime context. This research is descriptive to determine students' initial understanding of the basic concept of static fluids. This research involved 66 first-year students in biology education as research subjects. The data collection technique used in this research is a test that uses 6 questions that represent the concepts of density, hydrostatic pressure, and buoyant force. Data was analyzed descriptively, quantitatively and qualitatively. The research results show that many students still experience problems understanding the basic concepts of static fluids, including density, hydrostatic pressure, and buoyant force. This indicates the need for implementing learning that can improve students' understanding of basic concepts of static fluid and enable them to link their knowledge with conditions and situations related to the maritime context in their daily lives. One of the effective approaches to address this issue is implementing a problem-based learning model. This study highlights the importance of contextualized general physics instruction to bridge students’ experiential and conceptual understanding, especially in maritime-based learning contexts.